2020
DOI: 10.1186/s13031-020-00315-8
|View full text |Cite
|
Sign up to set email alerts
|

Researching the delivery of health and nutrition interventions for women and children in the context of armed conflict: lessons on research challenges and strategies from BRANCH Consortium case studies of Somalia, Mali, Pakistan and Afghanistan

Abstract: Background The BRANCH Consortium recently conducted 10 mixed-methods case studies to investigate the provision of health and nutrition interventions for women and children in conflict-affected countries, aiming to better understand the dominant influences on humanitarian health actors’ programmatic decision-making and how such actors surmount intervention delivery barriers. In this paper, the research challenges encountered and the mitigating strategies employed by the case study investigators in four of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This case study was developed to reflect on the complex operational environment in which a COVID-19 prospective cohort study was conducted within two humanitarian settings in Sub-Saharan Africa. The operational challenges and good practices identified–primarily in relation to participant recruitment and study management–were in general not specific to COVID-19, and have been identified in previous research carried out in the midst of epidemics [ 5 8 ]. However, the global impact of COVID-19, its high public profile, and specific pandemic policies appear to have exacerbated these problems and contributed to a final sample that underrepresented lower income individuals and nationals, and resulted in lower rates of enrollment than planned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case study was developed to reflect on the complex operational environment in which a COVID-19 prospective cohort study was conducted within two humanitarian settings in Sub-Saharan Africa. The operational challenges and good practices identified–primarily in relation to participant recruitment and study management–were in general not specific to COVID-19, and have been identified in previous research carried out in the midst of epidemics [ 5 8 ]. However, the global impact of COVID-19, its high public profile, and specific pandemic policies appear to have exacerbated these problems and contributed to a final sample that underrepresented lower income individuals and nationals, and resulted in lower rates of enrollment than planned.…”
Section: Discussionmentioning
confidence: 99%
“…Most African research on COVID-19 has been clustered in South Africa, Egypt, and Nigeria, translating to a paucity of evidence from humanitarian settings where populations often present with different risk profiles and health characteristics and where health services are more limited [ 4 ]. This may be partly attributable to specific challenges of pandemic research, as well as difficulties that have been previously identified in designing and managing robust studies in emergency settings [ 5 8 ]. However, little documentation exists describing the realities of COVID-19 research in these types of environments.…”
Section: Introductionmentioning
confidence: 99%
“…29 These conflicts range from agitation for resource control in the oil-rich Niger Delta region, to farmers-herders clashes in the Middle Belt region, to communal clashes and religious fundamentalism in the North. 2,29,30 However, since 2009, the Islamic fundamentalist terror group, Boko Haram (BH), has added a new dimension to the conflicts and has engaged the Nigerian state in the northern part of the country in the most violent armed conflict since the country's civil war. [30][31][32] The insurgency started in Maiduguri, Borno State, in 2009 and spread to other parts of Northern Nigeria.…”
Section: Contextmentioning
confidence: 99%
“…Selection bias across time and regions could arise if the composition of the sample in the conflict and non-conflict areas changes, for instance, due to population movement to and from the conflict area, in the period before and during the insurgency. 2 In our model, of particular concern is the fact that information about previous locations and reasons for migration of respondents is not available in the demographic health survey (DHS) and therefore, difficult to ascertain whether or not migration is due to the conflict. Also, the descriptive statistics in Figure 1 suggest some baseline differences (e.g., household wealth, household size etc.…”
Section: Model Specification and Estimation Strategymentioning
confidence: 99%
See 1 more Smart Citation